2014
DOI: 10.1209/0295-5075/106/43001
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-rotation resonances with subnatural widths using a control laser

Abstract: We demonstrate extremely narrow resonances for polarization rotation in an atomic vapor. The resonances are created using a strong control laser on the same transition, which polarizes the atoms due to optical pumping among the magnetic sublevels. As the power in the control laser is increased, successively higher-order nested polarization rotation resonances are created, with progressively narrower linewidths. We study these resonances in the D2 line of Rb in a room temperature vapor cell, and demonstrate a w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The PRS due to coherence effects of the EIT of Rb atoms with V-type configuration [10] have also been studied. Polarization-rotation resonances with sub-natural widths in the D2 line of the 87 Rb atom have been observed and analyzed with a simple model [7]. Autler-Townes splitting of a polarization rotation signal in the high-pumping power regime has also been observed [12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The PRS due to coherence effects of the EIT of Rb atoms with V-type configuration [10] have also been studied. Polarization-rotation resonances with sub-natural widths in the D2 line of the 87 Rb atom have been observed and analyzed with a simple model [7]. Autler-Townes splitting of a polarization rotation signal in the high-pumping power regime has also been observed [12].…”
Section: Introductionmentioning
confidence: 98%
“…The degree of rotation of another counter-propagating linearly polarized probe laser beam resonant on the same transition line is measured. Investigations of such birefringent anisotropy have focused on optical pumping [7], coherences [8], and saturation effects [9], etc. Various combinations of propagating directions [10], polarizations [11], and powers [12] for pump and probe laser beams have also been utilized to investigate various spectral shapes of polarization-rotation signals since the initial observation of the PRS.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a circularly polarized control light plays the role of a static magnetic field via a Zeeman-like ac Stark interaction and induces the optical Faraday rotation of the probe light 29 . Recently, the polarization rotation with the subnatural width, in the absence of the static magnetic field, has been reported at room temperature and the several 10 −3 rad rotation has been measured in the hyperfine transition of the Rb vapor cell 30 . More recently, the effect of microwave field on the nonlinear optically induced Faraday rotation was presented and it was demonstrated that the optical activity due to the enhanced birefringence can be generated in a wide range of frequency 31 .…”
Section: Introductionmentioning
confidence: 99%
“…They studied their system in a ladder configuration. Polarization-rotation has also been studied in a L -V type system of the Rb D 2 transition in room temperature vapour cell [13]. Polarization effects in the interaction between multi-level atoms and two optical fields has also been studied in 85 Rb in a Λ type and a ladder type configuration [14].…”
Section: Introductionmentioning
confidence: 99%